Cooperation in developing a disaster prevention and response plan for Arctic shipping. (June 2018) - Mileski, Joan; Gharehgozli, Amir; Ghoram, Lawrence; Swaney, Ryan
Abstract: The melting Arctic ice creates opportunities in cargo and passenger shipping for the international maritime community. Considering the circumpolar circumstances, the growth in Arctic shipping can result in a higher risk of mishaps and disasters. Disaster response may be more complex due to harsh, unpredictable weather conditions, varying stakeholders, differing political systems from the border countries and the disputed accountability for costs. Planning for an Arctic disaster is a 'wicked problem.' A 'wicked problem' is one that is difficult or impossible to solve because of incomplete, contradictory, and changing requirements that are often difficult to recognize. These conditions are due to the complexity of stakeholder interdependencies, environmental conditions, social/cultural/political concerns, and economic risks. The 'wicked problem' context helps to view decisions made on disaster prevention and response plans for Arctic shipping in terms of mitigation and minimization of the extent and duration of the negative consequences, rather than with a solution mindset. To achieve this goal, cooperation strategies are developed. This study maintains that cooperation among involved stakeholders is the most effective mechanism for an appropriate prevention and response plan. Cooperation not only increases effectiveness, but also the speed of response. Highlights: The melting Arctic ice creates cargo and passenger shipping opportunities. The rapid-changing and dangerous nature of the Arctic can result in a higher risk of disasters. Cooperation is required in order to mitigate disasters effects in the Arctic.